2020
DOI: 10.1177/1750458920950652
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous versus oral paracetamol for postoperative analgesia: A systematic review

Abstract: Paracetamol is a widely used analgesic agent that can be given by several different routes of administration. In the surgical setting, intravenous infusions of paracetamol are used, but an alternative is using oral paracetamol as a premedication. This systematic review is the first to compare the relative efficacy of intravenous and oral paracetamol at providing postoperative analgesia. Nine relevant studies were identified. Intravenous paracetamol resulted in a postoperative pain score of 0.5 points lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…This study reported almost 11 % non-conformity of Paracetamol use in terms of dosage, duration and contraindication. This result can be related to the systematic use of Paracetamol in hospitals based on its beneficial effect of reducing the pain score of 0.5 in postoperative patients 30 . Nevertheless, when assessing the contraindication of non-steroidal anti-inflammatory drugs, only 2 % of non-conformity was noted.…”
Section: Discussionmentioning
confidence: 90%
“…This study reported almost 11 % non-conformity of Paracetamol use in terms of dosage, duration and contraindication. This result can be related to the systematic use of Paracetamol in hospitals based on its beneficial effect of reducing the pain score of 0.5 in postoperative patients 30 . Nevertheless, when assessing the contraindication of non-steroidal anti-inflammatory drugs, only 2 % of non-conformity was noted.…”
Section: Discussionmentioning
confidence: 90%
“…Paracetamol powszechnie stosowany jako lek przeciwbólowy może być użyty w premedykacji zarówno drogą dożylną, jak i doustną. Sugeruje się, że obie formy mają podobny efekt działania [61]. Wydaje się, że w drobnych zabiegach operacyjnych paracetamol może być równie skuteczny jak opioidy, co ważne -nie niosąc skutków ubocznych, jak np.…”
Section: Leki Przeciwbóloweunclassified
“…Previously, paracetamol was manufactured for oral and rectal use; however, an intravenous (IV) formulation has also been available. A previous systematic review comparing the analgesic efficacy of IV paracetamol to oral paracetamol reported that IV paracetamol offered better postoperative pain than oral paracetamol [ 4 ]. On the contrary, Mallama and colleagues found no difference in postoperative pain between the IV and oral paracetamol groups [ 5 ].…”
Section: Introductionmentioning
confidence: 99%